Framing Analysis of the Kompas Daily on the News Coverage of One Year of the Prabowo–Gibran Administration (Zhongdang Pan and Gerald M. Kosicki Model Analysis) - Alif Alqausar (Journal of linguistics, culture and communication, 2025)
This research analyzes how the Kompas Daily frames the Prabowo-Gibran administration in its special edition marking their one year in office. Data was collected from six main news articles in the Politics & Law and Economy & Business sections of this special edition. Using Zhongdang Pan and Gerald M. Kosicki's framing theory, the study examines how the news structure is constructed through four analytical devices: syntax, script, thematic, and rhetoric. The research results indicate that Kompas frames the Prabowo–Gibran administration in a critical-moderate manner, with the main focus on issues of elite consolidation, policy centralization, the paradox of economic etatism, and weak legal reform. Syntactically, the news highlights academic and bureaucratic official sources; thematically, it focuses on the dominance of central power; rhetorically, it uses specific metaphors and diction to strengthen the editorial position. In its presentation, the research findings show that Kompas serves as reflective journalism that seeks to maintain a balance between appreciating political stability and criticizing the symptoms of power centralization.